An Observational Study to Assess the Role of Poison Severity Score and Glasgow Coma Scale Scoring Systems in Predicting the Severity and Clinical Outcome of Organophosphorus Poisoning - Basavaraj. B; Santhosh K B (Academia Anesthesiologica International, 2020)
Background: Organophosphate (OP) chemicals have been the most frequently used insecticides for agricultural pests worldwide since the 1980s, with a high risk of acute and subacute toxicity in humans.1 OP compounds are employed as insecticides, pesticides, herbicides, and chemical warfare agents. Objectives: a. Evaluation of Poison Severity Score in patients with Organophosphorus poisoning. b. Evaluation of Glasgow Coma Scale in patients with Organophosphorus poisoning. c. To assess the utility of PSS and GCS scoring systems in predicting severity and clinical outcomes in OP poisoning. Subjects and Methods: A Clinical Prospective Observational Study. Study area: The study was conducted in the Department of Emergency Medicine. Study Period: 1 year. Study population: Patients above 18 years of age of either sex, presenting with organophosphorus poisoning admitted to the Emergency Department or ICU were included size: The study consisted of a total of 100 subjects. Sampling Technique: Simple Random technique. Results: Out of 100 patients, OP poisoning was seen more in males (53%) and most commonly seen in the age group of 21-30 years (51%). Prehospitalization period was <6 hrs in most of the patients (74%). The most common compound consumed in our study was Chlorpyriphos (17%). Most of the patients consumed 50 to 100 mL of poison (42%). 19% of the patients were alcoholics. PSS and GCS were estimated at admission and after 24 hrs of admission. A significant association was observed for PSS(P<0.001) and GCS(P<0.001) with the outcome of OP poisoning. The outcome was also found associated with male gender, alcoholics and amount of poison consumption. Conclusion: Poisoning severity score and Glasgow Coma Scale are very useful for predicting the severity and clinical outcome of poisoning in patients, especially during triage. Identification of severity at an early stage followed by prompt treatment can prevent the late respiratory and cardiac failures associated with OP poisoning.